Corporate Decision-making with Macroeconomic Uncertainty - Oxelheim, Lars; Wihlborg, Clas (Oxford University Press, 2007)
This book develops “Macroeconomic Uncertainty Strategy” (MUST) as a tool for coping with the impact of macroeconomic fluctuations on risk management, performance assessment, and strategies for value enhancement. The essential elements of a corporate strategy for managing uncertainty in the macroeconomic environment includes setting corporate objectives for risk management, measuring risk, choosing operational and financial instruments for risk management, filtering out macroeconomic influences on performance, and developing compensation schemes that enhance shareholder value when macroeconomic fluctuations bias performance measures. The information obtained through conventional accounting systems become seriously misleading in response to macroeconomic fluctuations with the consequence that alternative ways to obtain relevant information must be considered. Conventional measures of exchange rate, interest rate, and inflation risk are similarly misleading with the consequence that a comprehensive view of the macroeconomic impact on the firm—recognizing the interdependence between macroeconomic variables—must be developed. Most of all, strategies to deal with macroeconomic fluctuations should be considered on a strategic level in the firm in order to establish shareholder wealth maximization as the objective of risk management and reward systems. Shareholder wealth maximization also requires that external stakeholders obtain information that allows them to evaluate the competitiveness of the firm without obfuscation by macroeconomic events.
Keywords: macroeconomic uncertainty; performance assessment; performance filtering; accounting standards; economic exposure; executive compensation; exchange rate risk; interest rate risk; financial strategy